Hantavirus infection as a risk factor for chronic kidney disease of unknown aetiology (CKDu) and its prevalence in endemic areas of Sri Lanka since 2010 according to a retrospective serological analysis. Issue 12 (16th December 2022) - Gamage, Chandika D.; Nanayakkara, Shanika; Sarathkumara, Yomani D.; Muthusinghe, Devinda S.; Shimizu, Kenta; Arikawa, Jiro; Lokupathirage, Sithumini M. W.; Nanayakkara, Nishantha; Gunarathne, Lishanthe; Chandrajith, Rohana; Harada, Kouji H.; Koizumi, Akio; et al.
Abstract : Background. Chronic kidney disease of unknown aetiology (CKDu) is a major public health problem in Sri Lanka, especially among agrarian communities. Although the cause of CKDu is still unknown, hantavirus infection has been proposed as a risk factor. Methods. This study was performed using serological samples collected from two CKDu-endemic areas, Anuradhapura (2010) and Badulla districts (2010 and 2016), and a non-endemic area, Matale (2016) district. The presence of anti-Thailand orthohantavirus IgG antibodies was investigated in serum samples. Hantavirus seroprevalence and demographic data were epidemiologically analysed. Results. Seroprevalence was higher in CKDu patients (40.6–60.0 %) and healthy individuals in CKDu-endemic areas (17.6–25.5 %) than in healthy individuals in non-endemic areas (3.0 %). Statistically significant odds ratios (ORs) for hantavirus infection in CKDu patients were detected in CKDu-endemic areas [ORs: 3.2 and 3.1; 95 % confidence interval (CI): 1.8–5.5 and 1.8–5.2 in Anuradhapura and Badulla districts in 2010; and OR: 4.4, 95 % CI: 2.3–8.5 in 2016 in Badulla district). Furthermore, the OR for hantavirus infection in Badulla district has increased in the last decade from 3.1 (95 % CI: 1.8–5.3) to 4.4 (95 % CI: 2.3–8.5). Conclusion. Hantavirus infection has been prevalent in two distant CKDu-endemic areas since 2010. The observed significant association of hantavirus seropositivity with CKDu indicates a possible role of hantavirus infection in CKDu pathogenesis.